Numerical Simulation of the Transient Process of Power Failure in a Mixed Pump. (10th April 2013) - Ma, Xudan; Liu, Jintao; Wang, Leqin
Abstract : A hydraulic-force coupling method was used to simulate the transient process of power failure condition. Computational fluid dynamics (CFD) was used to study the three-dimensional (3D), unsteady, incompressible viscous flows in a mixed flow pump in power failure accident. The dynamic mesh (DM) method with nonconformal grid boundaries was applied to simulate the variation of rotational speed of the field around the impeller. User-defined function (UDF) was used to obtain the rotational speed by solving the momentum conservation equation. External characteristics, such as rotational speed, head, flow rate, and hydraulic torque, were obtained during the transient process. Numerical speed and flow rate were compared with results calculated by semiempirical equation and they were in good agreement. The differences between transient and quasisteady results were also studied. Transient head and quasisteady head did not differ too much. The reason that caused this deviation was theoretically analyzed. The difference was explained to be caused by the inertia effect of the fluid contained in the pump and the pipeline. Internal flow field was also shown. Relative velocity vectors showed that the stall form and existence time in transient simulation were different from those in the quasisteady simulation. It is suspected to be one reason for head deviation.